2016
DOI: 10.5604/17331331.1215607
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Bacteriocin Produced by Halotolerant Pediococcus acidilactici Strain QC38 Isolated from Traditional Cotija Cheese

Abstract: A b s t r a c tDuring a screening of lactic acid bacteria producing bacteriocin from Cotija cheese, the strain QC38 was isolated. Based on the 16S rRNA gene nucleotide sequencing (516 pb accession no KJ210322) and phylogenetic analysis, the isolate was identified as Pediococcus acidilactici. Neutralized cell-free supernatant was tested for antimicrobial activity against 17 Gram-negative and Gram-positive pathogens. Growth inhibition was achieved against Listeria monocytogenes (supplier or indication or source)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…cholerae O1 Ogawa . 50 The inhibitory activity of Pediococcus spp. (isolated from cheese) against Listeria species was reported by Cavicchioli et al 51 They indicated that bacteriocins produced by E .…”
Section: Activity Of Lab Against Foodborne Pathogensmentioning
confidence: 99%
“…cholerae O1 Ogawa . 50 The inhibitory activity of Pediococcus spp. (isolated from cheese) against Listeria species was reported by Cavicchioli et al 51 They indicated that bacteriocins produced by E .…”
Section: Activity Of Lab Against Foodborne Pathogensmentioning
confidence: 99%
“…Usually, in the selection process, the first step of the screening process relies on the detection of inhibitory zones after cultivation in laboratory media ( Schillinger and Lucke, 1989 ; Sobrino et al, 1991 ; Larsen et al, 1993 ; Villani et al, 1994 ; Coventry et al, 1997 ). Lately, several diffusion methods were still successfully applied, such as the spot-on-lawn ( Morales-Estrada et al, 2016 ), the well-diffusion ( Lakshminarayanan et al, 2013 ; Nami et al, 2015 ), or the Oxford cup methods ( Bian et al, 2016 ). At the end of this step, the number of candidates is markedly lowered, thus allowing to reduce the workload in the following steps.…”
Section: Introductionmentioning
confidence: 99%
“…Ped. acidilactici QC38 which produces the bacteriocin Pediocin PA-1 was isolated from Cotija cheese, a ripened artisanal product of raw milk, produced in the state of Michoacán [ 48 ]. Ent.…”
Section: Cheeses As Sources Of Bacteriocin-producing Labmentioning
confidence: 99%
“…aureus, Salm. Ttyphimurium, V ibrio vulnificus, V. cholera (2 strains) LAB was able to grow in 1–9% NaCl concentration and harbored a plasmid that contains a gene for a pediocin (PA-1) [ 48 ] Chinese Tibet cheese Ent. faecium T1 Enterocin T1 LAB grown in MRS (37 °C, 24 h).…”
Section: Production Purification and Characterization Of Bacteriocinsmentioning
confidence: 99%